Historia kolekcji papirusów Biblioteki Uniwersyteckiej w Giessen - Kotyl, Marcin (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
The collection in Giessen numbers over 2800 papyri (including the set of P.Giss. 1080 items, P.Iand. 1157 and P.B.U.G. 596) and is one of the biggest and most important in the world. All the artefacts originate in Egypt and most of them were bought by Ernst Kornemann and Karl Kalbfleisch, members of the German Papyrus Syndicate (Deutsches Papyruskartell).
Keywords: papirusy greckie; Uniwersytet w Giessen; Deutsches Papyruskartell